Produtividade e composição bromatológica de monocultivos e consorciações de sorgo e milho com adubos verdes em diferentes épocas de corte - Silva, Paulo Claudeir Gomes (2009)
The project goal was to study the productivity and quality of forage produced bromatological from monoculture of sorghum and maize and intercropping of them with dwarf pea, sunn hemp, white lupine, sunflower and radish. The experiment was installed in the area of agricultural production of the Campus II Unoeste in Presidente Prudente-SP, on April 3rd, 2008. The experimental design was a split plot with four replications, with the following treatments: monoculture of sorghum (Sorghum bicolor) and maize (Zea mays) and sorghum consortium + pigeon pea (Cajanus cajan var. Dwarf) sorghum + sunn hemp (Crotalaria juncea), Sorghum + Sunflower (Helianthus annuus), sorghum fodder radish (Raphanus sativus), sorghum + white lupine (Lupinus albus), maize + pigeon pea dwarf, corn / sunn hemp, corn / sunflower corn + radish and corn + white lupine. The plots were scaled with eight rows of sowing of six meters. Biomass were collected at 60, 90 and 120 days after sowing for the quantification of plant material and chemical analysis. Statistical analysis consists of analysis of variance and Tukey test at 5% probability to compare treatment means. The single or intercropped sorghum was more efficient during low nutritive value, especially for syndications with sunflower, hemp and pigeon, which may have occurred because plants are more adapted to the dry climate of the region. Since the time of cutting that stood out with a productive balance and quality of the composition was 90 DAS.